1961
DOI: 10.1002/lipi.19610630303
|View full text |Cite
|
Sign up to set email alerts
|

Über den Chemismus der Farbreaktion von 2‐Thiobarbitursäure mit Carbonyl‐Verbindungen

Abstract: Anhand der Ergebnisse systematischer Untersuchungen uber die Reaktion zwiscben 2-Thiobarbitursaure (TBS) und definierten, als Modelle ausgewahlten Carbonyl-Verbindungen sowie naturlichen Substraten wird iiber die Spezifitat dieser Farbreaktion, iiber Struktur, Eigenschaften und Bildungsbedingungen der entstehenden Farbstoffe sowie uber die analytischen Anwendungsmoglichkeiten berichtet. Chemistry of the Colour-Reaction of 2-Thiobarbituric Acid with Carbonyl CompoundsFrom the results at hand of the systematic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1961
1961
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Numerous variations in the procedure of the TBA test are suggested in the literature (2). To increase the sensitivity, an addition of Fe +3 ions (19,20) is recommended. The reason for higher values is due to the breakdown of peroxides to products which react with TBA (9,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous variations in the procedure of the TBA test are suggested in the literature (2). To increase the sensitivity, an addition of Fe +3 ions (19,20) is recommended. The reason for higher values is due to the breakdown of peroxides to products which react with TBA (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for higher values is due to the breakdown of peroxides to products which react with TBA (9,21). Besides this, the possibility cannot be excluded that under drastic reaction conditions the sample is further autoxidized or that fat accompanying substances influence the TBA test (19,22). Since in this case there is no real increase in sensitivity, a procedure for the TBA reaction (9,10) was chosen in which acid and Fe + 3 ions were not present.…”
Section: Discussionmentioning
confidence: 99%
“…In these test systems it appears that a TBA adduct is formed with malondialdehyde (MDA) which is released from precursor molecules during the a&d heating stage of the test [2,3]. Several other aldehydes as well as the bile pigments give similar chromogenic adducts with TBA [4,5]. However, these can be distinguished from the MDA-TBA adduct following chromatographic separation or characterisation of their fluorescent spectra [61.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…The OH' radical is probably formed by the reaction sequence shown in eq. (3)(4)(5). Autoxidation of Cu(I) will lead to the formation of superoxide radicals which rapidly dismutate to form hydrogen peroxide.…”
Section: Effect Of Free Radical Scavengers On the Copperdependent Dammentioning
confidence: 99%
“…However, secondary products from linoleic acid also form a red pigment with the TBA test. It has been reported that 2,4-alkadienal forms the red pigment, but the red pigment formed by 2,4-alkadienal was suggested to be caused by further oxidation of alkadienal to malonaldehyde (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%